2015
DOI: 10.1103/physrevlett.114.071801
|View full text |Cite
|
Sign up to set email alerts
|

Right-Handed Quark Mixing in Left-Right Symmetric Theory

Abstract: We give exact formulas for the right-handed analog of the CKM matrix in the minimal Left-Right symmetric theory, for the case when the Left-Right symmetry is generalized Parity as in the original version of the theory. We derive its explicit form and give a physical reason for the known and surprising fact that the right-handed mixing angles are close in value to the CKM ones, in spite of the Left-Right symmetry being badly broken in nature. We exemplify our results on the production of the right-handed charge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 44 publications
0
105
1
Order By: Relevance
“…Additionally, the see-saw mechanism comes in rather naturally in the context of left-right symmetric scenarios; aside from other nice features, as for instance the recovery of parity symmetry, and the appearance of right-handed currents at high energy, which also makes such extensions very appealing. Recently, the left-right scenarios have been revised [15][16][17][18][19][20][21][22][23][24][25] in order to make contact with the latest experimental data of LHC. Moreover, the dark matter problem [26][27][28] and the diphoton excess anomaly [29][30][31][32][33] have been explored in this kind of scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the see-saw mechanism comes in rather naturally in the context of left-right symmetric scenarios; aside from other nice features, as for instance the recovery of parity symmetry, and the appearance of right-handed currents at high energy, which also makes such extensions very appealing. Recently, the left-right scenarios have been revised [15][16][17][18][19][20][21][22][23][24][25] in order to make contact with the latest experimental data of LHC. Moreover, the dark matter problem [26][27][28] and the diphoton excess anomaly [29][30][31][32][33] have been explored in this kind of scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…After pair-production from Higgs decay, each N decays to a charged lepton and two jets via W R , with a RH charged current quark flavour structure essentially identical to the left-handed one [42]. Due to the Majorana nature of N , 50% of events will result in a final state of two same-sign leptons and four jets with no missing energy, explicitly signalling LNV.…”
Section: Lepton Number Violating Higgs Decay At the Lhcmentioning
confidence: 99%
“…First, finally the LHC has a potential of observing it which makes it more timely than ever. Second, there have been two fundamental developments in recent years that make the theory self-contained and predictive: (i) the testable Higgs origin of neutrino mass [6], in complete analogy with the Standard Model case of charged fermions (ii) the analytic expression for the right-handed quark mixing matrix [7], a challenge that lasted some forty years. Moreover, there has been a furry of activity devoted to the LHC potential and the low energy processes such as neutrinoless double beta decay, lepton flavor violation and such.…”
Section: General Viewmentioning
confidence: 99%
“…Numerical calculations indicated that the LH and RH mixing angles were similar, but the first serious attempt to compute V R was made only some ten years ago [37], in a limited portion of parameter space and not as clearly as one would have hoped for direct application. The task was finally completed two years ago, when the analytic form valid in the entire parameter space was finally obtained [7] The leading form is given by simple (4), used in Introduction to anticipate the discussion. For a complete form and extensive discussion see [7] where the leading terms are derived for the differences between mixing angles …”
Section: Lrsm Is a Theory Of Rh Quark Mixing Anglesmentioning
confidence: 99%
See 1 more Smart Citation